Statutes of the Province of Ontario (Queen's Printer, 1868)
Prefixed to the first vol. is "An act for the union of Canada, Nova Scotia, and New Brunswick ... 29th March, 1867" with special t.p.: Anno regni Victoriæ, Britanniarum reginæ, tricesimo et tricesimo-primo. At a Parliament begun and holden at Westminster ... Toronto, 1868. 45 p.